2017
DOI: 10.1021/jacs.6b11595
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecularly “Caged” Carbon Nanoparticles for Intracellular Trafficking via Switchable Photoluminescence

Abstract: Reversible switching of photoluminescence (PL) of carbon nanoparticles (CNP) can be achieved with counterionic macromolecular caging and decaging at the nanoscale. A negatively charged uncoated, "bare" CNP with high luminescence loses its PL when positively charged macromolecules are wrapped around its surface. Prepared caged carbons could regain their emission only through interaction with anionic surfactant molecules, representing anionic amphiphiles of endocytic membranes. This process could be verified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 27 publications
1
54
0
Order By: Relevance
“…Our findings of excitation dependent and red shifted optical properties are in good agreement with earlier reports ,,. It is anticipated that effective conjugation of –C=C– group combined with increasing degree of surface oxidation in CDs could account for the large amount red shifting in FL spectra upon different excitation ,,. It is interesting to note that optical analysis of CDs showed CDs are multicolor in nature due to characteristic surface functionalities along with excitation dependent red shifted emission.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings of excitation dependent and red shifted optical properties are in good agreement with earlier reports ,,. It is anticipated that effective conjugation of –C=C– group combined with increasing degree of surface oxidation in CDs could account for the large amount red shifting in FL spectra upon different excitation ,,. It is interesting to note that optical analysis of CDs showed CDs are multicolor in nature due to characteristic surface functionalities along with excitation dependent red shifted emission.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of I D / I G was found to increase from 0.89 to 1.12 from CNP BI1 to CNP BI6 which could be attributed that the amorphous structures of CNPs are closely correlated to the red shift in PL emission . The FT‐IR spectra shown in Figure B reveal that all the passivated CNP BIs possessed abundant hydrophilic groups such as OH and NH (3425 cm −1 ), and COOH (1680 cm −1 ) on their surface ensuring their dispersibility in aqueous media . One interesting feature is the increase in the OH vibration bands at ≈3400 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Number of reports points to the fact these artificial band gaps lead characteristics strong UV absorption, blue‐to‐green PL, excitation‐energy‐dependent PL, etc. We and others have previously confirmed that the tunability of color of PL is directly associated with the energy gap between two different energy levels primarily originating from their surface states . CNPs are known to possess a variety of surface functional groups, defects, and adsorbates .…”
Section: Introductionmentioning
confidence: 94%
“…Regarding PCa and BC applications utilizing carbon-based NPs there is an increasing number of publications during the last couple of years, both for imaging and therapy but also for different kind of electrochemical biosensor systems [226,227,228,229,230,231,232,233,234]. For instance, regarding PCa, Heydari-Bafrooei et al and Pan et al have both developed different kind of CNT-based biosensor systems able to detect prostate specific antigen (PSA) in serum and vascular endothelial growth factor (VEGF) and PSA in serum, respectively, for early diagnosis of PCa [227,229].…”
Section: Nanoparticles For Prostate and Breast Cancermentioning
confidence: 99%